Diagnostic and prognostic impact of circulating YKL-40, IL-6, and CA 19.9 in patients with pancreatic cancer - Schultz, Nicolai A.; Christensen, Ib J.; Werner, Jens; Giese, Nathalia; Jensen, Benny V.; Larsen, Ole; Bjerregaard, Jon K.; Pfeiffer, Per; Calatayud, Dan; Nielsen, Svend E.; Yilmaz, Mette K.; Holländer, Niels H.; et al. (PLOS ONE, 2013)
Purpose: We tested the hypothesis that high plasma YKL-40 and IL-6 associate with pancreatic cancer and short overall survival. Patients and Methods: In all, 559 patients with pancreatic cancer from prospective biomarker studies from Denmark (n = 448) and Germany (n = 111) were studied. Plasma YKL-40 and IL-6 were determined by ELISAs and serum CA 19.9 by chemiluminescent immunometric assay. Results: Odds ratios (ORs) for prediction of pancreatic cancer were significant for all biomarkers, with CA 19.9 having the highest AUC (CA 19.9: OR = 2.28, 95% CI 1.97 to 2.68, p<0.0001, AUC = 0.94; YKL-40: OR = 4.50, 3.99 to 5.08, p<0.0001, AUC = 0.87; IL-6: OR = 3.68, 3.08 to 4.44, p<0.0001, AUC = 0.87). Multivariate Cox analysis (YKL-40, IL-6, CA 19.9, age, stage, gender) in patients operated on showed that high preoperative IL-6 and CA 19.9 (dichotomized according to normal values) were independently associated with short overall survival (CA 19.9: HR = 2.51, 1.22-5.15, p = 0.013; IL-6: HR = 2.03, 1.11 to 3.70, p = 0.021). Multivariate Cox analysis of non-operable patients (Stage IIB-IV) showed that high pre-treatment levels of each biomarker were independently associated with short overall survival (YKL-40: HR = 1.30, 1.03 to 1.64, p = 0.029; IL-6: HR = 1.71, 1.33 to 2.20, p<0.0001; CA 19.9: HR = 1.54, 1.06 to 2.24, p = 0.022). Patients with preoperative elevation of both IL-6 and CA 19.9 had shorter overall survival (p<0.005) compared to patients with normal levels of both biomarkers (45% vs. 92% alive after 12 months). Conclusions: Plasma YKL-40 and IL-6 had less diagnostic impact than CA 19.9. Combination of pretreatment YKL-40, IL-6, and CA 19.9 may have clinical value to identify pancreatic cancer patients with the poorest prognosis.
Gesehen am 26.07.2021